Eksistensi Seni Pertunjukan Peresean pada Masyarakat Sasak Lombok - Solikatun, Solikatun; Karyadi, Lalu Wirasapta; Wijayanti, Ika (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2019)
Culture is the product of human creation, feeling, and will. Culture is now shifting, for example, the shift of peresean tradition in Lombok sasak community. Through this study, the author is expected to find out the existence of peresean tradition and the meaning of peresean tradition to the community. This employed an explorative qualitative research method. The research took place in Karek Village, Praya Barat Daya Sub District, Lombok Tengah Regency. The subject of research was Darek villagers, in this case, taken using snowball sampling technique. The result of research showed that Peresean tradition is a traditional art of Sasak ethnic community in which two men are fighting against each other (pepadu) using weapon made of rattan stick and shield. In peresean tradition, there are rule and sanction in its implementation. Peresean performance is now conducted at certain times, e.g. on village or regency anniversary day, wedding party, low-season, RI independence day, or in guest welcoming event. Values contained in peresean tradition are life values including appreciating fraternity, friendship, economy, kinship, belief, culture, and art value. Meanwhile, the meaning ofperesean tradition includes a means of showing off man’s bravery, agility, and sturdiness, martial art, sportsmanship spirit, selfappreciation, establishing good relationship, and friendship. So, peresean traditional performance art in Sasak Lombok ethnic community has shifted viewed from its rule, meaning, and implementation time aspects.